2019
DOI: 10.1136/bmjopen-2019-030046
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from ramping up a Canadian Take Home Naloxone programme during a public health emergency: a mixed-methods study

Abstract: ObjectivesThis study describes the 2016 expansion of the British Columbia Take Home Naloxone (BCTHN) programme quantitatively and explores the challenges, facilitators and successes during the ramp up from the perspectives of programme stakeholders.DesignMixed-methods study.SettingThe BCTHN programme was implemented in 2012 to reduce opioid overdose deaths by providing naloxone kits and overdose recognition and response training in BC, Canada. An increase in the number of overdose deaths in 2016 in BC led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…While all Canadian provinces and territories have publicly funded THN programs, research and evaluation of these programs in the scholarly literature is limited. A recent study from Ontario describes uptake of the province’s pharmacy-dispensed naloxone kits in Ontario [ 27 ], and preliminary analyses of provincial THN programs in Ontario [ 28 ], Alberta [ 29 ], Manitoba [ 30 ], and British Columbia [ 15 ] have been published. Data from other jurisdictions are not directly comparable, due to differences in program structure, eligibility criteria, and scope [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While all Canadian provinces and territories have publicly funded THN programs, research and evaluation of these programs in the scholarly literature is limited. A recent study from Ontario describes uptake of the province’s pharmacy-dispensed naloxone kits in Ontario [ 27 ], and preliminary analyses of provincial THN programs in Ontario [ 28 ], Alberta [ 29 ], Manitoba [ 30 ], and British Columbia [ 15 ] have been published. Data from other jurisdictions are not directly comparable, due to differences in program structure, eligibility criteria, and scope [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…analyses of provincial THN programs in Ontario [28], Alberta [29], Manitoba [30], and British Columbia [15] have been published. Data from other jurisdictions are not directly comparable, due to differences in program structure, eligibility criteria, and scope [9].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Among others, this includes the BC take-home naloxone (THN) program, expanded opioid agonist treatment (OAT) availability, and observed consumption sites, all of which had a significant impact on preventing overdose deaths [ 14 ]. The THN program, for instance, has been responsive to the overdose crisis by getting naloxone kits into the hands of those that need it most [ 15 , 16 ], with more than 53,000 THN kits reported as used to reverse an overdose between 2017 and 2019 [ 17 ]. However, it is important to note that someone else must be present for naloxone to be administered to an individual experiencing an overdose.…”
Section: Introductionmentioning
confidence: 99%
“…7 In Canada specifically, a British Columbia THN program providing low-barrier access to naloxone kits at no cost greatly reduced the number of deaths due to OIRD during a time when there was an increase in the number of fentanyl-related toxicities. 8-10 This THN program, launched in 2012, originally provided naloxone through harm reduction sites and community organizations where there was a high prevalence of OIRD. In December 2017, the program incorporated selected community pharmacies to provide naloxone to other places and populations with limited access to THN kits. Distribution records from participating pharmacies indicated that 3523 kits were distributed by 562 pharmacies between January 1, 2018, and December 31, 2018.…”
Section: Effectiveness Of Naloxone Distribution Programsmentioning
confidence: 99%